Acceleration of wound healing potential of Benzyl N'-(Indol-3-Ylinethylidene)-Hydrazinecarbodithioate derivatives in experimental rats - Mughrabi, F.F.; Ali, Hapipah Mohd; Khaledi, H.; Ameen, M.; Hashim, H. (2010)
The effects of topical application of Benzyl N'-(indol-3-Ylmethylidene)-Hydrazinecarbodithioate derivatives (BHC) on the process of wound healing enclosure and histology of healed wound were assessed. Five groups of adult male Sprague Dawley rats, all animals were experimentally wound in the posterior neck area About 0.2 rnL of 10% Tween 20 solution was applied to the wound of Group 1 animals (negative control). Intrasitegel was applied topically to wounds of Group 2 animals as reference. About 0.2 mL of 25, 50 and 100 mg mL -1 of compound derivative were applied to the wounds of Group 3, 4 and 5, respectively. Macroscopically, wound dressed with compound derivative significantly healed earlier than those treated with 10% Tween 20 solution. Also wound dressed with 100 mg mL -1 compound derivative accelerate the rate of wound healing compared to those dressed with Intrasite and 25 and 50 mg mL -1 compound derivative. Histological analysis of healed wounds dresses with compound derivative showed comparatively less scar width at wound enclosure and healed wound contained less macrophages and large amount of collagen with angiogenesis compared to wounds dressed with 10% Tween 20 solution. In conclusion, wounds dressed with 100 mg mL -1 of compound derivative significantly enhanced the acceleration of the rate of wound healing enclosure and histologically healed wounds contain comparatively less macrophages and more collagen with angiogenesis. © Medwell Journals, 2010.